Fragility: the social dislocation through stabilized narratives - Wentz, Fabiana; Volmer, Lovani; Martins, Rosemari Lorenz (Revista Crioula, 2023)
This article aims to analyze the short story Fragilidade, by Jane Tutikian, to understand how the narratives stabilized in this text contribute to the social dislocation of characters. Based on theories of authors such as Bachelar, Bhabha, Cassirer, Said, Pesavento, Moresco and Ribeiro, and Espig, this study proposes relation among memory, identity and imaginary and the past revealed in protagonist’s narrative.